(3JQJjH MSfs - (3eMSf Hf MSjf GdLdjdjs
(3ChdgG (B:s
(3GdMeOddg GdPi CYLR GdHdZGA HcJGHg hCcQe CQHGH GdHUGFQ HNWGHg hcTa dge Yf CSJGQ MLGHg s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3Hg fXGe GdJYbjHIs
(3JMJhi Ydi agQS ddcJGHs
(3hYdjgG hba deOQSI GdMSfjI SfI (B1232 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
Keywords: (3GdJaSjQ hYdhe GdbQBfs